Rubisco Assembly in the Chloroplast - Vitlin Gruber, Anna; Feiz, Leila (Frontiers in Molecular Biosciences, 2018)
Abstract Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) catalyzes the rate-limiting step in the Calvin-Benson cycle, which transforms atmospheric carbon into a biologically useful carbon source. The slow catalytic rate of Rubisco and low substrate specificity necessitate the production of high levels of this enzyme. In order to engineer a more efficient plant Rubisco, we need to better understand its folding and assembly process. Form I Rubisco, found in green algae and vascular plants, is a hexadecamer composed of 8 large subunits (RbcL), encoded by the chloroplast genome and 8 small, nuclear-encoded subunits (RbcS). Unlike its cyanobacterial homolog, which can be reconstituted in vitro or in E. coli, assisted by bacterial chaperonins (GroEL-GroES) and the RbcX chaperone, biogenesis of functional chloroplast Rubisco requires Cpn60-Cpn20, the chloroplast homologs of GroEL-GroES, and additional auxiliary factors, including Rubisco accumulation factor 1 (Raf1), Rubisco accumulation factor 2 (Raf2) and Bundle sheath defective 2 (Bsd2). The discovery and characterization of these factors paved the way for Arabidopsis Rubisco assembly in E. coli. In the present review, we discuss the uniqueness of hetero-oligomeric chaperonin complex for RbcL folding, as well as the sequential or concurrent actions of the post-chaperonin chaperones in holoenzyme assembly. The exact stages at which each assembly factor functions are yet to be determined. Expression of Arabidopsis Rubisco in E. coli provided some insight regarding the potential roles for Raf1 and RbcX in facilitating RbcL oligomerization, for Bsd2 in stabilizing the oligomeric core prior to holoenzyme assembly, and for Raf2 in interacting with both RbcL and RbcS. In the long term, functional characterization of each known factor along with the potential discovery and characterization of additional factors will set the stage for designing more efficient plants, with a greater biomass, for use in biofuels and sustenance.